Analytic image reconstruction from partial data for a single‐scan cone‐beam CT with scatter correction. Issue 11 (22nd October 2015) - Min, Jonghwan; Pua, Rizza; Kim, Insoo; Han, Bumsoo; Cho, Seungryong
Abstract : Purpose: A beam‐blocker composed of multiple strips is a useful gadget for scatter correction and/or for dose reduction in cone‐beam CT (CBCT). However, the use of such a beam‐blocker would yield cone‐beam data that can be challenging for accurate image reconstruction from a single scan in the filtered‐backprojection framework. The focus of the work was to develop an analytic image reconstruction method for CBCT that can be directly applied to partially blocked cone‐beam data in conjunction with the scatter correction. Methods: The authors developed a rebinned backprojection‐filteration (BPF) algorithm for reconstructing images from the partially blocked cone‐beam data in a circular scan. The authors also proposed a beam‐blocking geometry considering data redundancy such that an efficient scatter estimate can be acquired and sufficient data for BPF image reconstruction can be secured at the same time from a single scan without using any blocker motion. Additionally, scatter correction method and noise reduction scheme have been developed. The authors have performed both simulation and experimental studies to validate the rebinned BPF algorithm for image reconstruction from partially blocked cone‐beam data. Quantitative evaluations of the reconstructed image quality were performed in the experimental studies. Results: The simulation study revealed that the developed reconstruction algorithm successfully reconstructs the images from the partial cone‐beam data. In the experimental study, the proposed method effectively corrected for the scatter in each projection and reconstructed scatter‐corrected images from a single scan. Reduction of cupping artifacts and an enhancement of the image contrast have been demonstrated. The image contrast has increased by a factor of about 2, and the image accuracy in terms of root‐mean‐square‐error with respect to the fan‐beam CT image has increased by more than 30%. Conclusions: The authors have successfully demonstrated that the proposed scanning method and image reconstruction algorithm can effectively estimate the scatter in cone‐beam projections and produce tomographic images of nearly scatter‐free quality. The authors believe that the proposed method would provide a fast and efficient CBCT scanning option to various applications particularly including head‐and‐neck scan.